2010
DOI: 10.1111/j.1469-7580.2010.01248.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic morphological changes in the skulls of mice mimicking human Apert syndrome resulting from gain‐of‐function mutation of FGFR2 (P253R)

Abstract: Apert syndrome is caused mainly by gain-of-function mutations of fibroblast growth factor receptor 2. We have generated a mouse model (Fgfr2 + ⁄ P253R) mimicking human Apert syndrome resulting from fibroblast growth factor receptor 2 Pro253Arg mutation using the knock-in approach. This mouse model in general has the characteristic skull morphology similar to that in humans with Apert syndrome. To characterize the detailed changes of form in the overall skull and its major anatomic structures, euclidean distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…The correspondence between Apert syndrome mouse models and human patients with Apert syndrome has been demonstrated at the morphological, histological and molecular levels (Chen et al, 2003; Wang et al, 2005; Wang et al, 2010; Holmes et al, 2009; Aldridge et al, 2010; Du et al, 2010; Martínez-Abadías et al, 2010; Martínez-Abadías et al, 2011), validating the use of large experimentally controlled samples of mouse models to elucidate the complex etiology of Apert syndrome.…”
Section: Introductionmentioning
confidence: 81%
“…The correspondence between Apert syndrome mouse models and human patients with Apert syndrome has been demonstrated at the morphological, histological and molecular levels (Chen et al, 2003; Wang et al, 2005; Wang et al, 2010; Holmes et al, 2009; Aldridge et al, 2010; Du et al, 2010; Martínez-Abadías et al, 2010; Martínez-Abadías et al, 2011), validating the use of large experimentally controlled samples of mouse models to elucidate the complex etiology of Apert syndrome.…”
Section: Introductionmentioning
confidence: 81%
“…Furthermore, it's noticed that the phenotypes of each mutant strain just partially resembled the skull malformation of EIIa-253 mice, suggesting that the malformation of specific tissues partially contributed to dysmorphogenesis of skull of AS mice (Fig. 7E)16, 21, 36, 37, and that the maldevelopment of AS head is caused by the combined effects of abnormal development of calvarias, cranial base, brain and other tissues (Fig. 7D).…”
Section: Resultsmentioning
confidence: 98%
“…In previous reports, Apert syndrome mouse models with ubiquitous expression of mutant FGFR2 generated using EIIa-Cre (such as EIIa-Fgfr2 +/P253R, abbreviated as EIIa-253) exhibited smaller body size, shorter cranial dimensions along the rostrocaudal axis and broader breadth of the frontal bone than wild-type littermates 10, 12, 16. In this study, Col2a1-253 mice showed normal life span with normal body size and AS-like skull dysmorphology compared with wild-type mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations